The changing face of African agriculture in an era of rural transformation: Dynamics in land system and tenure policies - Jayne, Thomas S.; Muyanga, Milu; Wineman, Ayala; Ghebru, Hosaena; Stevens, Caleb (Michigan State University, 2019)
Sub-Saharan Africa is witnessing rapid changes in farm size distributions. “Medium-scale” farm landholdings of five to 100 hectares now account for a substantial and growing share of farmland in many African countries. 1 Since 2000, this category of African farmer has acquired more land and put much more new land under cultivation than large-scale foreign investors. In parallel to these developments, the region is witnessing changes in land tenure institutions that influence who is acquiring land (Ghebru and Girmachew, 2019a; 2019b). Parts of the region are experiencing a notable shift in the allocation of customary land from a rights-based approach that secures access to land for localborn members of the community to market-based approaches to land allocation based increasingly on willingness to pay. As population densities rise and land becomes scarce in many areas, tenure security is becoming increasingly important. Research evidence shows that security of tenure typically promotes long-term land investments and agricultural productivity, hence the need for African governments to focus on improving land tenure security to more effectively achieve their national agricultural policy objectives.